Self Efficacy sebagai Variabel Intervening dalam Mempengaruhi Servant Leadership terhadap Perilaku Kewarganegaraan Organisasi: (Studi Pegawai Dinas Lingkungan Hidup Kabupaten Muaro Jambi) - Amelinda Amelinda; Shofia Amin; Rts Ratnawati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine the role of self-efficacy as an intervening variable in influencing the relationship between servant leadership and organizational citizenship behavior (OCB) among employees of the Muaro Jambi Regency Environmental Service. The approach used in this study was quantitative with a survey method. Data were collected through distributing questionnaires using a Likert scale to 56 employees who were sampled in this study. The statistical analysis technique used was Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, which was managed using SmartPLS 4.1.1. The results of the study indicate that servant leadership has a positive and significant influence on organizational citizenship behavior, as well as on self-efficacy. In addition, self-efficacy was also found to have a positive and significant influence on organizational citizenship behavior. These findings also confirm that self-efficacy significantly mediates the influence of servant leadership on organizational citizenship behavior. This study contributes to understanding the role of servant leadership in improving the quality of organizational citizenship behavior by increasing individual self-confidence in the workplace. The recommendation from the results of this study is the importance of developing self-efficacy in an effort to increase positive employee behavior in government organizations.